BLENDING OF JATROPHA OIL WITH OTHER VEGETABLE OILS TO IMPROVE COLD FLOW PROPERTIES AND OXIDATIVE STABILITY OF ITS BIODIESEL - Dwi Setyaningsih, Erliza Hambali, Sri Yuliani dan Djajeng Sumangat (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT Jatropha oil has rich in unsaturated fatty acids, but other tropical oils, such as palm oil and coconut oil, have high saturated fatty acid. Blending of jatropha biodiesel with soybean, rapeseed, palm and coconut biodiesels resulted in different propertie, between properties of each pure compounds or even better than pure biodiesel. Jatropha biodiesel in concentration of 50-70% jatropha-coconut blend had better cloud point and pour point (9 oC and -6 oC, respectively), compare to jatropha biodiesel (12 oC, 0 oC) and coconut biodiesel (15 oC, 9 oC). Blending of jatropha and coconut were further investigated using two methods, namely methods 1 was in the form of biodiesel and method 2 was in the form of oil before biodiesel processing. Blending method 2 resulted in higher cloud point and lower pour point compared to method 1 and the values were relatively constant. Blending of 55% of jatropha biodiesel with lauric biodiesel (75% lauric methylester) showed a minimum cloud point and pour point (-3 oC; -18 oC). This minimum point called eutectic point expressed an ideal equilibrium of liquid-solid among saturated medium chain alkyl esters and unsaturated long chain alkyl esters. Methylester composition of this biodiesel was 34.03% lauric, 0.31% miristic, 8.91% palmitic, 3.82% stearic and 46.17% oleic acids. This proved the important role of lauric acid, a medium chain saturated fatty acid, which was dominant in coconut biodiesel (48.11%). Keyword: jatropha biodiesel, blending, cloud point, pour point